Evidence-based healthcare chaplaincy : a research reader - Fitchett, George, 1948-; White, Kelsey B.; Lyndes, Kathryn (Jessica Kingsley Publishers, 2018)
Research literacy is now a requirement for Board-Certified chaplains in the US and a growing field in the UK. This reader gives an overview and introduction to the field of healthcare chaplaincy research. The 21 carefully chosen articles in this book illustrate techniques critical to chaplaincy research: case studies; qualitative research; cross-sectional and longitudinal quantitative research, and randomized clinical trials. The selected articles also address wide-ranging topics in chaplaincy research for a comprehensive overview of the field. To help readers engage with the research, each article includes a discussion guide highlighting crucial content, as well as important background information and implications for further research. This book is the perfect primary text for healthcare chaplaincy research courses, bringing together key articles from peer-reviewed journals in one student-friendly format.